Fault geometry and kinematics of the 2021 Mw 7.3 Maduo earthquake from aftershocks and InSAR observations - Fan, Xiaoran; Zhang, Guohong; Zhao, Dezheng; Xie, Chaodi; Huang, Chuanchao; Shan, Xinjian (Frontiers in Earth Science, 2022)
The 2021 Mw 7.3 Maduo earthquake revealed the significant seismic hazard of faults developed within the Bayan Har Block of eastern Tibet, China (e.g., the Kunlun Pass–Jiangcuo Fault). Relocated aftershock data are in good agreement with the Interferometric Synthetic Aperture Radar (InSAR) coseismic displacement field and field investigations. In this study, we used aftershock point cloud fitting to model the relocated aftershocks of the Maduo earthquake, and obtained the detailed geometry and characteristics of the seismogenic fault. Based on InSAR coseismic deformation, the geometric model of the seismogenic fault and its slip distribution were retrieved. The results show that this event was shallow (0–10 km) and characterized by sinistral strike-slip motion. We identified four asperities along the fault strike; the maximum slip of 4.84 m occurred on the eastern segment of the fault, in an area where the strike changed. The results suggest that the central segment of the main seismogenic fault is mature and smooth, while western and eastern segments are complex and immature. The seismic risk on the eastern section of the East Kunlun fault zone is of particular concern.